Dal‐induced red blood cell incompatibilities in a Doberman Pinscher with von Willebrand factor deficiency and ehrlichiosis. Issue 2 (29th October 2020) - Conti‐Patara, Andreza; Ngwenyama, Thandeka R.; Martin, Linda G.; Wardrop, K. Jane
Abstract: Objective: To describe a complex case involving the management of a dog with von Willebrand disease (vWD), active ehrlichiosis infection, nonregenerative anemia, and blood type incompatibility related to the Dal antigen. Case Summary: A 13‐week‐oldintact male Doberman Pinscher weighing 7.2 kg was presented to the emergency service for a previous hemorrhaging event and progressive nonregenerative anemia. The dog had received a fresh whole blood transfusion 8 days prior to presentation due to severe anemia. Upon presentation, the puppy was tachycardic, and his mucous membranes were pale. A CBC revealed a nonregenerative anemia with a PCV of 0.11 L/L (11%). von Willebrand factor deficiency was suspected and later confirmed. The dog's blood type was dog erythrocyte antigen (DEA) 1 positive, but cross‐matching to 4 RBC units, both DEA 1 positive and negative, failed to yield any compatible units. Antibody against a possible Dal RBC antigen was suspected, and 11 blood donors (Dalmatians and Dobermans) were cross‐matched to find 2 compatible donors. After an uneventful fresh whole blood transfusion, a bone marrow biopsy revealed a hypocellular bone marrow and erythroid hypoplasia. A SNAP4DxPlus test and subsequent polymerase chain reaction (PCR) testing were positive for Ehrlichia ewingii and E. canis . Treatment with doxycycline was started, and the PCV was 0.17 L/L (17%) at discharge. At the 1‐week follow‐up, the PCV was 0.24 L/L (24%), and the puppy was doing well. New or Unique Information Provided: This is a unique case of a dog presenting with several challenging disorders, including vWD resulting in hemorrhage, ehrlichiosis potentially contributing to a nonregenerative anemia, and a blood type incompatibility due to the Dal antigen. Doberman Pinschers have a high prevalence of vWD‐ and Dal ‐negative phenotype, which emphasizes the value of cross‐matching and the recognition of antigen prevalence in specific breeds.